Andreas Capellanus, Scholasticism, and the Courtly Tradition - Monson, Don Alfred (Book collections on Project MUSE., 2005)
"This book, the first study in English devoted entirely to Andreas Capellanus's De Amore, presents a comprehensive inquiry into the influence of scholasticism on the structure and organization of the work, applying methods of medieval philosophy and intellectual history to an important problem in medieval literary studies. Eschewing polemics over authorial intentions, Don Monson develops an approach to the work's meaning through an examination of its form."--Jacket